If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -5) + -4(x + 6) = 3x + 4 Reorder the terms: x(-5 + x) + -4(x + 6) = 3x + 4 (-5 * x + x * x) + -4(x + 6) = 3x + 4 (-5x + x2) + -4(x + 6) = 3x + 4 Reorder the terms: -5x + x2 + -4(6 + x) = 3x + 4 -5x + x2 + (6 * -4 + x * -4) = 3x + 4 -5x + x2 + (-24 + -4x) = 3x + 4 Reorder the terms: -24 + -5x + -4x + x2 = 3x + 4 Combine like terms: -5x + -4x = -9x -24 + -9x + x2 = 3x + 4 Reorder the terms: -24 + -9x + x2 = 4 + 3x Solving -24 + -9x + x2 = 4 + 3x Solving for variable 'x'. Reorder the terms: -24 + -4 + -9x + -3x + x2 = 4 + 3x + -4 + -3x Combine like terms: -24 + -4 = -28 -28 + -9x + -3x + x2 = 4 + 3x + -4 + -3x Combine like terms: -9x + -3x = -12x -28 + -12x + x2 = 4 + 3x + -4 + -3x Reorder the terms: -28 + -12x + x2 = 4 + -4 + 3x + -3x Combine like terms: 4 + -4 = 0 -28 + -12x + x2 = 0 + 3x + -3x -28 + -12x + x2 = 3x + -3x Combine like terms: 3x + -3x = 0 -28 + -12x + x2 = 0 Factor a trinomial. (-2 + -1x)(14 + -1x) = 0Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(14 + -1x)' equal to zero and attempt to solve: Simplifying 14 + -1x = 0 Solving 14 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -1x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -1x = 0 + -14 -1x = 0 + -14 Combine like terms: 0 + -14 = -14 -1x = -14 Divide each side by '-1'. x = 14 Simplifying x = 14Solution
x = {-2, 14}
| 5(e+4)=45 | | 20-2p=12 | | n-(-1)=45 | | 4(2x-3)=3+8x | | 9x-y=33 | | x+3=2(3x-3) | | x=8+-3x | | 35t=70 | | -4+11q=-92 | | (3b-3)(4b-5)= | | 5=6(x+8)-5x | | 81g-11g-45g+(-85)=40 | | -58a-65a+100a=46 | | z+17=-8 | | -[5z-(11z+10)]=10+(5z+8) | | 2+-3x+2x^2+x^3= | | 5X=8X+27 | | 20m-2.25=2.75 | | -18a+(-58)=32 | | 9(5x-6)-44x=2 | | 0.5x-3.3=0.7 | | -0.2t^2+5.2t=17.6 | | 8+(-3k)-20-3k-(-1)= | | 25-.21x=19.75 | | 18m+13=22 | | 4x-16= | | 9x-4=34 | | 10+6h=64 | | -11+m/6=0 | | x^2-1x=12 | | 6y+3y=12 | | 6-X=X |